Epistemic Beliefs and Pre-service Teachers’ Conceptions of History Instruction - Paricio, Javier; García-Ceballos, Silvia; Rubio-Navarro, Alodia (Frontiers in Education, 2022)
This study investigates the difficulties pre-service history teachers face in understanding and implementing a history curriculum focused on historical reasoning. Based on the general hypothesis of beliefs exerting a direct influence on teachers’ actions, this study provides a qualitative analysis of the epistemic and learning/teaching conceptions on which pre-service teachers base their reflections and decisions when they have to produce a teaching plan for a specific situation. The outcome of the first phases of the analysis was a new theoretical reference framework that innovated by simultaneously analyzing epistemic and educational conceptions. On the one hand, the analysis results include a considerable number of pre-service teachers who use epistemic beliefs identifying history and the past when addressing the curriculum. On the other, none of them, not even those with advanced epistemic beliefs, think about the curriculum in terms of an inquiry-based approach to historical problems, and, therefore, they display a transmissive–reproductive conception of history instruction. Consequently, the main contribution is observation of a twofold threshold that pre-service teachers must cross to understand and accept an interpretive history curriculum: they must overcome the identification between past and history and instead immerse themselves in the necessarily interpretive nature of any history; and they must stop viewing learning as knowledge internalization and reproduction and, instead, embrace a conception of learning as inquiry and reasoning.